B.L.A.C.K an aboriginal song of hip hop - Saunders, Grant Leigh; Australian Film Television and Radio School (Australia : The Australian Film Television and Radio School, 2005)
This is a musical documentary that exposes an authentic and empowering B.L.A.C.K. voice existing underneath the hype of'bling-bling' hip hop. This is a film with rhythm, rhyme and reason
Title from title screen
Co-producer, Roslyn Baker ; camera, Trevor Almeida ; sound designer, Grant Leigh Saunders
DVD Format
Keywords: Black race; Blacks; Rap (Music)